2006
DOI: 10.1021/jf061794p
|View full text |Cite
|
Sign up to set email alerts
|

Potide-G Derived from Potato (Solanum tuberosum L.) Is Active against Potato Virus YO (PVYO) Infection

Abstract: A PVYO virus-resistant potato (Solanum tuberosum L. cv. Golden Valley) was identified, and further, from its tubers, a small (5.57 kDa) antiviral peptide potide-G was isolated. Application of potide-G on virus susceptible potato (cv. Winter valley) expressed robust resistance to PVYO infection and showed no virus infected morphology. We found that PVYO infection spreads up completely within 3 days post inoculation (dpi) in susceptible cultivar. PVYO was more accumulated toward the basal leaves, when infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Results of real-time PCR showed that the application of 10 μg of purified potide-G was sufficient to reduce virus accumulation by 50% on average from the PVY infection in susceptible “Winter Valley” cultivars. The authors have reported that this peptide isolated from resistant potatoes offers new opportunities for the development of new biological pesticides against plant viruses (Tripathi et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Results of real-time PCR showed that the application of 10 μg of purified potide-G was sufficient to reduce virus accumulation by 50% on average from the PVY infection in susceptible “Winter Valley” cultivars. The authors have reported that this peptide isolated from resistant potatoes offers new opportunities for the development of new biological pesticides against plant viruses (Tripathi et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…The entire inoculation was conducted using a syringe to reduce damage to the leaf surface. The 'Winter Valley' variant was shown to be highly susceptible to PVY O infection with the development of local disease symptoms, expressed as the appearance of leaf burching and crinkling, mild to strong yellow leaf mosaic, necrotic veins, leaf spots, and leaf dropping . However, the infected 'Winter Valley'-G cultivar did not show any symptoms after PVY O infection, over the entire life of the plant (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…When S. tuberosum L. 'Golden Valley' was infected with PVY O , the Ry gene was highly up-regulated and the CP gene could not be detected via real-time PCR and ELISA . Moreover, we also obtained sufficient results for antiviral activity from the application of the 'Golden Valley' protein and potide-G, a small (5.57 kDa) antiviral peptide isolated from the 'Golden Valley' cultivar . Therefore, we have focused on the 'Golden Valley' Ry gene ( G-Ry ) in an effort to improve resistance against PVY O infection for agricultural applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of germination of hyphae and fungal spore was the possible mechanism of AHPs's antifungal activity (Fernańdez et al, 2012). In 2006, two antiviral peptides named potide-G and golden peptide were ) that showed promising antiviral activity against potato virus YO (PVYO) (Tripathi et al, 2006). Another study with C. annum found a new antimicrobial protein CaAMP1 that exhibited promising activity against both different bacteria (MICs 5-30 µg/ml) and fungi (MICs 5-100 µg/ml).…”
Section: Plant Name Traditional Uses Referencesmentioning
confidence: 99%